Dry Preparation of Trichoderma Species Promotes Significant Decrease of Fusarium oxysporum in Shallot Cultivation (Allium ascalonicum) - Nika, Distira Viro; Singkam, Abdul Rahman; Andayani, Shinta (Universitas Islam Negeri Ar-Raniry, 2025)
Shallot is a horticultural plant that is susceptible to pathogen attacks. The continuous use of non-biological fungicides has a negative impact on the environment, making it necessary to implement biological control using antagonistic microorganisms. This study aims to evaluate the differences in growth and yield of shallots treated with a dry formulation of Trichoderma sp. to control Fusarium wilt. The study was conducted using a Randomized Block Design (RBD) with four treatments and six replications. The concentrations used were 0 grams/liter, 7 grams/liter, 14 grams/liter, and 21 grams/liter. The data analysis results showed that the dry formulation of Trichoderma sp. at a concentration of 21 grams/liter was the most effective in controlling Fusarium wilt, with the lowest disease severity of 23.16 (F_1,24=47.61, p